2018
DOI: 10.2478/macvetrev-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastrointestinal Parasitism Infections in Cattle of Bass Kabylie Area: Case of Bejaia Province, Algeria

Abstract: The objective of this study was to determine the prevalence, identification of species and the dynamics of gastrointestinal (GI) parasites during humid and dry seasons in local cattle of different ages. The study was carried out in the Province of Bejaia, Algeria from December 2013 to June 2014. A total of 143 fecal samples were collected from different cattle herds. Fecal samples were visually examined then observed using flotation and sedimentation microscopic techniques. Eggs and worms were identified accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
1
11
1
Order By: Relevance
“…A study in Bangladesh found S. papillosus in 8.5 % of 117 samples of feces of cattle from a state dairy farm (Paul et al, 2016). Th e analysis of 143 samples of feces of cattle in Algeria in 2013-2014 found S. papillosus in 1.3 % of cases (Moussouni et al, 2018). Over the analysis of 185 samples of feces in the suburbs of Bangkok in 2014, S. papillosus was found in 16.8 % of goats (Azrul et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Bangladesh found S. papillosus in 8.5 % of 117 samples of feces of cattle from a state dairy farm (Paul et al, 2016). Th e analysis of 143 samples of feces of cattle in Algeria in 2013-2014 found S. papillosus in 1.3 % of cases (Moussouni et al, 2018). Over the analysis of 185 samples of feces in the suburbs of Bangkok in 2014, S. papillosus was found in 16.8 % of goats (Azrul et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of helminth infections in livestock productivity in some countries has been established, such as retarded growth, weight loss, reduced food consumption, lower milk production, impaired fertility, and high mortality rates in cases of massive infections (1). A recent study in Algeria (Bass Kabylie region) demonstrates that digestive strongyles are the most prevalent species in cattle (2). This infection is generally controlled by synthetic drugs; however, excessive use of such drugs has led to widespread resistance.…”
mentioning
confidence: 99%
“…Also, it was reported that fasciolosis remained common in Algeria in ruminants, particularly in the north and causes direct losses due to the high rate of condemnation of infected livers (Ouchene-Khelifi et al, 2018). Several investigations done in Algeria revealed that there was often a polyparasitism (Boulkaboul and Moulaye, 2006;Saidi et al, 2009;Moussouni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that animal species influences, in general, the rate and the type of parasitic infection. Furthermore, the epidemiology of infections with gastrointestinal parasites (GIP) in livestock varies depending on the prevailing weather conditions and management practices (Moussouni et al 2018). Variance analysis of annual parasite dynamics has shown a significant seasonal effect for some parasite species (Meradi, 2012;Titi et al 2014).…”
Section: Introductionmentioning
confidence: 99%